Penerapan Terapi Dzikir Untuk Mereduksi Self Injury ( Pada Klien “Y” di Desa Seri Kembang Kecamatan Payaraman Kabupaten Ogan Ilir) - Alpionita, Pini; Razzaq, Abdur; Noviza, Neni (Jurnal Ilmu Sosial, Humaniora dan Seni, 2024)
This research is entitled "Application of Dhikr Therapy to Reduce Self-Injury (In Client "Y" in Seri Kembang Village, Payaraman District, Ogan Ilir Regency). This research aims to determine self-injury. To find out the causal factors and to find out how to apply morning dhikr bismikallah therapy to client "Y". The research approach used in this research is a qualitative approach with a type of research (field research). The subject in this research is client "Y" who experienced self-injury in Seri Kembang Village, Payaraman District, Ogan Ilir Regency. The data collection methods in this research are observation, interviews and documentation, while the data analysis techniques used are pattern matching, data explanation, time series analysis. The results of the research concluded that the self-injury behavior of client "Y" was that there was a change in behavior that appeared when his wishes were not followed, such as easily feeling emotional, angry, disappointed, having difficulty controlling himself and always being alone and keeping all his problems to himself and ending up injuring his wrist. hands, banging hands against the wall, hitting the wall. The application of dhikr therapy is the discipline of praying five times a day, morning dhikr and reciting the Koran. By implementing this dhikr therapy, the client gradually experiences changes. And this therapy is used to provide calm within the client after experiencing feelings that conflict with him to better accept reality and face the problems he is facing, because Dhikr is a process of self-awareness as a servant of Allah SWT.